Quantitative Effects of Repeated Muscle Vibrations on Gait Pattern in a 5-Year-Old Child with Cerebral Palsy - Filippo Camerota; Manuela Galli; Claudia Celletti; Sara Vimercati; Veronica Cimolin; Nunzio Tenore; Guido M. Filippi; Giorgio Albertini (Case Reports in Medicine)
Objective. To investigate quantitatively and objectively the effects of repeated muscle vibration (rMV) of triceps surae on the gait pattern in a 5-year-old patient with Cerebral Palsy with equinus foot deformity due to calf spasticity. Methods. The patient was assessed before and one month after the rMV treatment using Gait Analysis. Results. rMV had positive effects on the patient's gait pattern, as for spatio-temporal parameters (the stance duration and the step length increased their values after the treatment) and kinematics. The pelvic tilt reduced its anteversion and the hip reduced the high flexion evidenced at baseline; the knee and the ankle gained a more physiological pattern bilaterally. The Gillette Gait Index showed a significant reduction of its value bilaterally, representing a global improvement of the child's gait pattern. Conclusions. The rMV technique seems to be an effective option for the gait pattern improvement in CP, which can be used also in very young patient. Significant improvements were displayed in terms of kinematics at all lower limb joints, not only at the joint directly involved by the treatment (i.e., ankle and knee joints) but also at proximal joints (i.e., pelvis and hip joint).